Perlindungan Hukum Pekerja yang Terkena Pemutusan Hubungan Kerja (PHK) untuk Mengambil Jaminan Hari Tua (JHT) Sebelum Berusia 56 Tahun dalam Permenaker 2/2022 - Mahayoni Mahayoni; Soraya Dewi Kartikasari (President University, 2019)
Social security is a crucial thing that everyone must have, as this has been regulated and guaranteed by the state, and the state has an obligation to fulfill the rights of these citizens. In connection with this matter, the Indonesian government has regulations regarding social security regulated in Law No. 40/2004 concerning the National Social Security System, including health insurance, work accident insurance, death security, and one that will be concern of discussion in this research is a program regarding Pension Security or commonly called Jamaican Hari Tua (JHT). The regulations regarding this matter have changed several times, but still aim to focus on ensuring that Indonesian citizens who are the JHT participants can enjoy a decent life after entering retirement. Provisions for disbursing funds for participants have changed from the initial regulations to the updated regulations, for example changes to implementing regulations regarding the JHT, namely the Ministerial Regulation of Manpower No 2/2022 concerning